2022
DOI: 10.52082/jssm.2022.91
|View full text |Cite
|
Sign up to set email alerts
|

Early Superimposed NMES Training is Effective to Improve Strength and Function Following ACL Reconstruction with Hamstring Graft regardless of Tendon Regeneration

Abstract: The study aimed at investigating the effects of neuromuscular electrical stimulation superimposed on functional exercises (NMES+) early after anterior cruciate ligament reconstruction (ACLr) with hamstring graft, on muscle strength, knee function, and morphology of thigh muscles and harvested tendons. Thirty-four participants were randomly allocated to either NMES+ group, who received standard rehabilitation with additional NMES of knee flexor and extensor muscles, superimposed on functional movements, or to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…NMES+ were administered either selectively for a specific muscle district/s (Amiridis et al, 2005; Bezerra et al, 2009, 2011; Celik et al, 2020; Feil et al, 2011; Herrero et al, 2010a, 2010b; Hwang et al, 2020; Labanca et al, 2018, 2022; Mathes et al, 2017; Paillard et al, 2005a; Pantović et al, 2015; Takano et al, 2010; Wirtz et al, 2016) or in a whole‐body configuration (Dörmann et al, 2019; D'Ottavio et al, 2019; Filipovic et al, 2019b; Ludwig et al, 2020; Micke et al, 2018; Pano‐Rodriguez et al, 2020; Teschler et al, 2021). Superimposed NMES targeted the following muscles: back extensors (Park et al, 2016); abdominals (Hwang et al, 2020); quadriceps femoris (Benavent‐Caballer et al, 2014; Bezerra et al, 2009, 2011; Celik et al, 2020; Feil et al, 2011; Herrero et al, 2010a, 2010b; Labanca et al, 2018, 2022; Mathes et al, 2017; Paillard et al, 2005a; Pantović et al, 2015; Takano et al, 2010), hamstrings (Bezerra et al, 2011; Labanca et al, 2022; Mathes et al, 2017; Wirtz et al, 2016), leg adductors (Wirtz et al, 2016); tibialis anterior (Amiridis et al, 2005; Wirtz et al, 2016), Triceps Surae (Mathes et al, 2017; Wirtz et al, 2016). The studies which applied whole‐body NMES+ adopted a similar electrodes configuration involving pectoral muscles, abdominal muscles, upper and lower back muscles, buttocks, anterior and posterior thigh muscles and lower leg muscles (Dörmann et al, 2019; D'Ottavio et al, 2019; Filipovic et al, 2019b...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NMES+ were administered either selectively for a specific muscle district/s (Amiridis et al, 2005; Bezerra et al, 2009, 2011; Celik et al, 2020; Feil et al, 2011; Herrero et al, 2010a, 2010b; Hwang et al, 2020; Labanca et al, 2018, 2022; Mathes et al, 2017; Paillard et al, 2005a; Pantović et al, 2015; Takano et al, 2010; Wirtz et al, 2016) or in a whole‐body configuration (Dörmann et al, 2019; D'Ottavio et al, 2019; Filipovic et al, 2019b; Ludwig et al, 2020; Micke et al, 2018; Pano‐Rodriguez et al, 2020; Teschler et al, 2021). Superimposed NMES targeted the following muscles: back extensors (Park et al, 2016); abdominals (Hwang et al, 2020); quadriceps femoris (Benavent‐Caballer et al, 2014; Bezerra et al, 2009, 2011; Celik et al, 2020; Feil et al, 2011; Herrero et al, 2010a, 2010b; Labanca et al, 2018, 2022; Mathes et al, 2017; Paillard et al, 2005a; Pantović et al, 2015; Takano et al, 2010), hamstrings (Bezerra et al, 2011; Labanca et al, 2022; Mathes et al, 2017; Wirtz et al, 2016), leg adductors (Wirtz et al, 2016); tibialis anterior (Amiridis et al, 2005; Wirtz et al, 2016), Triceps Surae (Mathes et al, 2017; Wirtz et al, 2016). The studies which applied whole‐body NMES+ adopted a similar electrodes configuration involving pectoral muscles, abdominal muscles, upper and lower back muscles, buttocks, anterior and posterior thigh muscles and lower leg muscles (Dörmann et al, 2019; D'Ottavio et al, 2019; Filipovic et al, 2019b...…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported increased muscle strength after a period of training that was based on NMES superimposed on the concentric and eccentric phase of functional dynamic exercises, which were performed in a closed kinetic chain fashion (Dörmann et al, 2019;Filipovic et al, 2019b;Labanca et al, 2018Labanca et al, , 2022Ludwig et al, 2020;Micke et al, 2018;Pantović et al, 2015). Specifically, Labanca et al showed that a rehabilitation treatment for ACL reconstructed patients, based on NMES+ superimposed on a sit-to-stand-to-sit exercise and delivered at the maximal tolerated current intensity, carried significant improvements in muscle strength of knee extensors and flexors and limb symmetry index compared to the same treatment but without electrical stimulation (Labanca et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral CMJ. Seven meta-analyses of 16 studies (37,38,(41)(42)(43)45,46,(52)(53)(54)(55)57,58,61,64,72) metrics. Reconstructed limbs showed lower jump heights (SMD = −0.86, 95% CI = −0.97, −0.75), RSI (SMD = −0.85, 95% CI = −1.05, −0.65), and longer contact times (SMD = 0.26, 95% CI = 0.08 to 0.43) than uninjured contralateral limbs.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, with NMES, it is possible to overcome patients’ inability to voluntarily activate muscles by means of externally elicited muscle contractions, which can be increased by increasing the intensity of stimulation [6]. Therefore, to maximize the effects on the neuromuscular system, NMES can be superimposed to isometric contractions [7] or easy functional movements that can be performed also by orthopaedic patients early after surgery [8,9]. Finally, the development of battery-powered electrical stimulators allows NMES-based rehabilitation to be carried out anywhere: in rehabilitation centres as well as at patients’ homes.…”
Section: Introductionmentioning
confidence: 99%